The Cancelled Text from John Foxe's 1572–73 edition of The Whole Workes of William Tyndall, John Frith, and Doctor Barnes. (23rd February 2019) - Rankin, Mark
Abstract: John Foxe's edition of The Whole Workes of William Tyndall, John Frith, and Doctor Barnes (1572‐73) represents the first printed version of the English reformer William Tyndale's theological and historical works. Its importance in aligning Tyndale with the priorities of the Elizabethan church has been acknowledged. Nearly all surviving copies of the book preserve a cancellans, or substitute leaf, at CC3 r in the Tyndale section, but three copies preserve the leaf in its initial state. Foxe extracted a portion of text on the original leaf from one of the prefaces of Tyndale's 1534 English New Testament. This material also appears at the front of the volume in all copies examined, where Foxe re-edited it. Comparison between the initial leaf and its substitute at CC3 r sheds new light on the evolution of the book in John Day's printing house and upon Foxe's priorities as a textual editor.